Analysis of the self-adherence to treatment and blood glucose monitoring in patients with diabetes mellitus - Amanda Marselin; Fajar Agung Dwi Hartanto; Maria Putri Sari Utami (Chronic Diseases Journal)
BACKGROUND: Patients with diabetes mellitus (DM) are increasing every year around the world, but only about 30% are taking medication regularly. The main goal of therapy in patients with DM is to normalize insulin activity and blood glucose levels without hypoglycemia to reduce neuropathic complications. Patients with DM must control their blood glucose levels regularly so that the value of blood glucose levels and adherence to treatment which are the main factors in the outcome of therapy are identified. The purpose of this study was to analyze the adherence of patients with DM to medication and monitoring blood glucose levels as part of self-adherence.